Traits of popular children: a case study - Ningrum, Diah; Ismail, Nik Ahmad Hisham (Sons and Daughters Publications, 2015)
To be accepted in peer groups is important in children adjustment particularly in the school and future social relationship in general. The aim of the study was to find out traits of popular children. Mixed methods were used in the present study, which had two phases, first quantitative method and second qualitative method. Peer matrix of peer nomination was used as Peer matrix of peer nomination was used as method of data collection in quantitative, meanwhile interviews and observation were used in qualitative method. The results revealed that 5 popular children obtained from peer matrix of peer nomination were liked most by peers. Moreover, these five popular children were known because they had traits that made them different from others. Peers viewed them based on positive traits and positive social interaction, physical interaction, the quality of relationship, and social dominance. The result also indicated that popular children gave effects on peers and school environment.